Using stable isotopes (δ2H, δ13C) to identify natal origins and larval host plant use by western bean cutworm, Striacosta albicosta (Lepidoptera: Noctuidae) captured in southern Ontario. (19th January 2022) - Hobson, Keith A.; Kusack, Jackson W.; Gootgarts, Jonathan; Longstaffe, Fred J.; McNeil, Jeremy N.
Abstract: The Western Bean Cutworm ( Striacosta albicosta, Smith), a significant agricultural pest, has a broad distribution in North America having recently expanded northeastward. However, while there are significant populations each summer in Ontario, Canada, this species has limited local overwintering capacity, which suggests a high proportion of immigrant moths. Knowing the origins of immigrant moths would provide insight into their migration and could assist in their management. We used stable‐hydrogen isotope ( δ 2 H) analyses of wings from 283 moths captured over a seven‐year period (2012–2020) to estimate origins of these individuals based on the well‐established precipitation isoscape for the continent. We also analysed wings for stable‐carbon isotopes ( δ 13 C) to examine host plant use as this species uses both C3 (e.g., beans) and C4 (e.g., corn) sources during larval development. Regardless of year, most moths (71%–91%) fed on corn as larvae. We combined this finding with δ 2 H analyses to narrow probable geographic natal origins by applying an informed prior to Bayesian‐based isotopic assignments by assuming the Corn Belt of the United States as the likely region of origin. This combined approach indicated Iowa, Missouri, Illinois, Indiana and Ohio as the most likely origins, a conclusion supported by analyses of wind trajectories on nights prior to high trap catches in our study area. While our combined approach narrowed down the possible origins of cutworms captured in southern Ontario, estimates of origin remain relatively broad and to be useful for management purposes future refinements will be required. Abstract : Stable H isotopes in precipitation and stable C isotopes in larval host plants are transferred to emergent adult moths. Using calibration relationships, we then depicted likely origins of moths entering Ontario based on continental precipitation patterns (H) and the extent of the US corn belt (C).